Structure and luminescence properties of a Nd3+ doped Bi4Ge3O12 scintillation crystal: new insights from a comprehensive study. Issue 12 (10th March 2017) - Chen, Feiyang; Ju, Meng; Gutsev, Gennady L.; Kuang, Xiaoyu; Lu, Cheng; Yeung, Yauyuen
Abstract : We have, for the first time, identified a unique semiconducting phase of the R 3 space group where impurity Nd 3+ ions occupy exactly the host Bi 3+ ion sites with trigonal symmetry. Abstract : The rare-earth Nd 3+ doped bismuth ortho-germanate Bi4 Ge3 O12 (BGO), serving as an excellent kind of fast scintillator, has been widely used in many scientific and technical areas. However, there are two unsolved problems which hinder its practical applications, namely: (i) there is no detailed information about the microstructure and location sites of Nd 3+ ions in the BGO lattice; (ii) it is difficult to determine the electric and magnetic dipole transition mechanisms of Nd 3+ doped BGO. Here, the microstructure and site location of Nd 3+ ions in BGO have been systematically investigated by means of an unbiased CALYPSO structure search method coupled with first principles calculations. As a result, we have for the first time identified a unique semiconducting phase of the R 3 space group where impurity Nd 3+ ions occupy exactly the host Bi 3+ ion sites with trigonal symmetry. Based on our developed WEPMD method, new sets of free-ion, crystal field and orthogonal correlation crystal field parameters are obtained, yielding a much better agreement between the calculated and observed values for both optical energy levels and Zeeman splitting g -factors of the ground state. Starting from these new set parameters, the majority of electric dipole and magnetic dipole transition lines, including a large number of absorption and emission lines, in the region of visible and near-infrared spectra of Nd 3+ ions in BGO are predicted and discussed. It is shown that the main emission channel of Nd 3+ doped BGO occurs at the inter-Stark laser transitions of 4 F3/2 → 4 I11/2 corresponding to an emission wavelength of approximately 1064 nm.